Uncobasidium roseocremeum sp. nov. and other corticioid basidiomycetes from the Patagonian Andes of Argentina - Gorjón, Sergio P. (2012)
Eighteen corticioid species are reported as new from the Patagonian Andes of Argentina, most of them new records for South America or for the southern hemisphere. Comments are included for all species with illustrations provided for some. Uncobasidium roseocremeum is described as new and a key to the accepted Uncobasidium species is included. © 2012. Mycotaxon, Ltd.